Clinical and immunological outcomes after randomized trial of baked milk oral immunotherapy for milk allergy - Dantzer, Jennifer A.; Lewis, Sloan A.; Psoter, Kevin J.; Sutherland, Aaron; Frazier, April; Richardson, Eve; Maiche, Synaida; Seumois, Gregory; Peters, Bjoern; Wood, Robert A. (JCI Insight, 2025)
BACKGROUND Cow’s milk (CM) allergy is the most common food allergy in young children. Treatment with oral immunotherapy (OIT) has shown efficacy, but high rates of adverse reactions. The aim of this study was to determine whether baked milk OIT (BMOIT) could reduce adverse reactions while still inducing desensitization, and to identify immunological correlates of successful BMOIT.METHODS This phase II, randomized trial evaluated the safety and efficacy of BMOIT in milk-allergic children 3–18 years old. After the initial placebo-controlled first year of treatment, placebo-treated participants crossed over to active BMOIT. Double-blind, placebo-controlled oral food challenges (OFCs) were conducted with BM after year 1 and to both BM and unheated milk (UM) after year 2. IgG and IgE antibodies were measured along with CM-specific (CM+) CD4+ memory T cell populations, profiled using flow cytometry and scRNA-Seq.RESULTS Twenty-one of 30 (70%) reached the primary endpoint of tolerating 4044 mg of BM protein at month 24, and 11 of 30 tolerated 2000 mg or more of UM protein. Dosing symptoms were common, but more than 98% were mild, with no severe reactions. Immunological changes associated with desensitization included increased CM IgG4, CM+ FOXP3+ cells, and Tregs and corresponding decreases in CM IgE, CM+ Th2A cells, and CD154+ cells. T cell and antibody measurements were combined to build a model that predicted UM OFC outcomes.CONCLUSION BMOIT was well tolerated and induced desensitization to BM and UM. This desensitization corresponded to redistribution within antigen-specific antibody and T cell compartments that provided insight into the mechanistic changes that occur with OIT treatment.TRIAL REGISTRATION ClinicalTrials.gov NCT03462030.FUNDING: Myra Reinhardt Family Foundation (grant number 128388), NIH/NIAID (U19AI135731, T32AI125179, S10OD025052)